Synthesis and Electrochemical Properties of New Derivatives of Dibenzo(perhydrotriazino)-aza-crown Ethers and Their Cobalt(II) Complexes - Banaei, Alireza; Karimi, Soheyla; Valizadeh, Maliheh (Asian Journal of Chemistry, 2017)
Four novel dibenzo(perhydrotriazino)-aza-crown ethers, L1, L2, L3 and L4 have been synthesized in good yield by petrenko-kritchenko condensation of bisaldehydes (a-d) with thiourea in the presence of ammonium acetate in the mixture of ethanol and acetic acid. Subsequently, crown ethers L1 and L2 were used as a precursor to synthesize cobalt complexes [Co(L1)2Cl2] and [Co(L2)2Cl2], respectively. The newly synthesized crown ethers have been characterized with the elemental analyses, melting point, IR, 1H NMR, 13C NMR and mass spectral data. The cobalt complexes of crown ethers have been characterized by IR spectra and elemental analyses. Also, electrochemical behaviour of these crown ethers and their cobalt(II) complexes was studied by cyclic voltammetry. The results showed that the electrochemical properties of the synthesized Co(II) complexes revealed the irreversible two electron transfer redox process.